2022
DOI: 10.3390/ijms23031100
|View full text |Cite
|
Sign up to set email alerts
|

The Missing Pieces to the Cold-Stored Platelet Puzzle

Abstract: Cold-stored platelets are making a comeback. They were abandoned in the late 1960s in favor of room-temperature stored platelets due to the need for longer post-transfusion platelet recoverability and survivability in patients with chronic thrombocytopenia. However, the current needs for platelet transfusions are rapidly changing. Today, more platelets are given to patients who are actively bleeding, such as ones receiving cardiac surgeries. It has been established that cold-stored platelets are more hemostati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 80 publications
1
9
0
1
Order By: Relevance
“…Indeed, in line with previous studies [9,10,16,18], both ADP-and TRAP-induced platelet aggregation in CSWB decreased already during 14-day storage. As platelets in CSWB are exposed to cold storage, this impaired aggregation is seemingly in contradiction with increased platelet activation and enhanced haemostatic capacity of cold-stored platelet concentrates [19,20], but in accordance with the finding of attenuated aggregation responses to ADP and TRAP in CSWB as compared to cold-stored platelet concentrates [10]. This implies that other CSWB components, namely, RBCs and plasma, may influence platelet functionality.…”
Section: Discussionsupporting
confidence: 73%
“…Indeed, in line with previous studies [9,10,16,18], both ADP-and TRAP-induced platelet aggregation in CSWB decreased already during 14-day storage. As platelets in CSWB are exposed to cold storage, this impaired aggregation is seemingly in contradiction with increased platelet activation and enhanced haemostatic capacity of cold-stored platelet concentrates [19,20], but in accordance with the finding of attenuated aggregation responses to ADP and TRAP in CSWB as compared to cold-stored platelet concentrates [10]. This implies that other CSWB components, namely, RBCs and plasma, may influence platelet functionality.…”
Section: Discussionsupporting
confidence: 73%
“…Similarly, lyophilized and cold-stored platelets could be an alternative for treatment of increased platelet consumption in acute hemorrhage. However, their safety and effectiveness in humans have still to be proven [ 35 , 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…PLT aggregation within PCs was not significantly increased in CS (Figure 5), as previously published data suggested. 8 Johnson et al 14 ; Reddoch et al 48 and others, summarised in a review by Zhao et al, 49 have reported that PLT aggregation in CS appears to be dependent on the PAS used, therefore comparisons across studies must be interpreted with caution. The biggest reported improvement when comparing aggregation between RT and CS platelets is related to ADP 8 ; however, ADP was not used in this study due to our observation that ADP was not able to induce aggregation from day 3 onwards (data not shown), as has been reported by others.…”
Section: Discussionmentioning
confidence: 99%